Impacts of Pig Farming on the Water Quality of Serin River, Sarawak - Ling, Teck Yee; Layang, H.W.; Then, Y.P.; Kasing, Apun (Universiti Kebangsaan Malaysia, 2006)
In Sarawak, pig farm operators are required to treat the wastewater containing pig waste and spilt food in oxidation ponds before discharge. However, information on the impact of this industry on surface water quality is lacking. Therefore,the objective of this study is to determine the impact of pig farm effluent on the water quality of Serin River and its tributaries. Results of analysis show that the tributary that received pond effluent has significantly higher mean of total suspended solids (TSS), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammonia-nitrogen(NH3-N), reactive phosphorus (SRP) and Escherichia coli (E. coli) concentrations when compared to those of the tributary that did not receive pond effluent. Comparisons between the stations upstream and downstream of the discharge point indicated that BOD5 and COD were significantly higher at the downstream station that received pond effluent. Dissolved oxygen (DO) was the lowest at the tributary receiving effluent from pig farms with a mean of2.40 mgll. According to the Interim Water Quality Standard of the Department of Environment, water quality at the tributary that received pig farm effluent falls into Class III whereas that of the other stations falls into Class II. It is recommended that further studies be conducted on the management of waste to explore the possibility of turning the waste into a resource so that water quality of rivers can remain pristine for drinking and recreation.